Konceptframtagning av huv till Picadelis nästa generations salladsbar - Lindqvist, Johan; Kader, Oskar (Chalmers tekniska högskola / Institutionen för industri- och materialvetenskap, 2019)
Abstract Picadeli is a company that provides grocery stores with salad bars and everything you need to create your own salad. The current salad bar is called Arctic. Some of the improvement areas were that the hood was used incorrectly, mechanical problems arose due to a lack of robustness, as well as sanitary aspects. The aim with this bachelor thesis work was to identify the improvement potential of the hood and opening mechanism and create two concepts in Solid Works. The two final concepts will partly be the basis for Picadeli when producing the next generation salad bar, which is currently referred to as "Polar". By using the methodology of Reverse engineering, a product development project has been executed, in which several concepts have been developed and compared to each other. Reverse engineering is a method that you use to develop an existing product by making careful observations of the current concept, evaluate the strength and weaknesses of the existing product. You also need to gather information from the affected parties. The project results in two final concepts. Concept 1 consists of a hood where only the front of the hood opens, and the sides remain in the same spots. The mechanical function depends on a constant force that is being applied in a vertical direction on a lever. The increase of torque is to counteract the weight of the hood. The constant torque is being applied by a torsion spring. In Concept 2 the whole hood is moved vertically by linear devices and linear motors. A motion sensor was applied to replace the handle. The process of selecting materials for the different parts resulted in PMMA plastic for the hood, and for handles and frames the choice became anodized aluminum. There is also some improvement potential for the material that the report suggests. The recommendations are to further develop these two concepts and the first step could be to create prototypes, calculate to ensure that the new salad bar is theoretically possible and then develop them towards finished ...